Borderland studies, frontierization, and the Middle East's in-between spaces. Issue 3 (26th May 2020) - Schofield, Richard
ABSTRACT: This paper provides a conclusion to a special issue of Mediterranean Politics that has sought to promote critical approaches for a better understanding of spatial process in some of the Middle East region's most prominent in-between spaces. Following recent efforts to observe bordering processes in and around the region, this collection develops the possibility that a subtly different process of territorialization is taking place in those spaces where state power is most challenged, compromised, and uncertain – frontierization. In assessing its possibilities, this paper highlights the significant record of past geographical approaches to borderlands but also selectively explores the established phenomenon of in-betweenness in the evolution of the regional territorial framework. It concludes by suggesting that any fresh consideration of contemporary spatial process should engage with geography's long tradition of studying borderlands as cooperative features and more recent multidisciplinary coverage that tends to view them today as spaces of insecurity in state margins beyond the reach of state authority. Any reinvigorated borderland studies – to which the idea of frontierization might well have something to say – needs to be multidisciplinary but also would do well to further develop agendas for exploring these regions that have been around for some time.